A quasi-experiment testing a public participation process for designing and implementing an enforcement program among minorities - Factor, Roni (Journal of experimental criminology, 2019)
The present study aimed at developing and empirically evaluating an innovative public participation process for designing and implementing a specially tailored traffic enforcement program in minority communities. During the multi-stage process, participants were actively involved in decision-making, including identifying “dark” hot spots—places where offenses and risky behavior recur but might not be known to the police—and designing a customized enforcement program and community projects.